AB1316 Hospital admission trends and short-term outcome for iga vasculitis in children and adults in western australia. (12th June 2018) - Nossent, J.; Raymond, W.; Keen, H.; Inderjeeth, C.; Preen, D.
Abstract : Background: Immunoglobulin A vasculitis (IgAV), formerly called Henoch-Schönlein purpura, is an immune complex mediated small-vessel vasculitis that preferentially affects the skin, intestines and kidneys. While more common in children, IgAV is not unusual in adults, where it has been associated with worse outcomes. Objectives: To compare hospital admission rates and outcomes over time between adult and paediatric inpatients with IgA vasculitis Methods: Data were extracted from a state-wide registry for all hospital admissions in Western Australia (WA) between 1980 to 2015 for patients with a primary or secondary diagnosis of IgAV (ICD-9-CM code 287.0/ICD-10-AM code D69.0). Paediatric cases were defined as those ≤19 years at first diagnosis. Results: From a total 764 patients admitted to hospital with an IgAV diagnosis 508 (66%) were paediatric and 256 (34%) adult cases. IgAV was the primary diagnosis in 463 (91.1%) paediatric and in 123 (48%) adult patients (p<0.01). In children, mean age at primary diagnosis was 5.6 years of (range 0–19) versus 50.2 years (range 20–91) in adults. Both groups had similar proportions of Indigenous (3.5 vs 1.6%, p=0.4) and male patients (59 vs 51.2%, p=0.3). Over the observation period, the annual rates per 100.000 for a first admission for IgAV declined from 4.2 to 0.4 for children and from 0.42 to 0.2 for adults, while length of stay in days decreased from 5.8 to 1.8 for children and increased from 10.5 to 21.1 for adults. Three adults (2.4%) but no child required ICU admission, while one adult (0.7%) and no child died in hospital. Readmission rates for IgAV were considerable and higher in children than adults (25.6% vs 18.7%, p=0.1). Conclusions: Admission rates for IgAV in children in WA have declined steeply over the last decades and now almost equate admission rates for adults. The reduction in length of stay and absence of in-hospital mortality support an increased willingness or necessity to manage children with IgAV outside the hospital setting despite a significant readmission rate. In contrast, hospital admission for IgAV in adults associates with prolonged lenth of stay and a slight risk for ICU admission and in-hospital mortality. Acknowledgements: Supported by an unrestricted grant from the Arthritis Foundation of Western Australia. We acknowledge the contribution by Data Linkage WA staff and custodians. Disclosure of Interest: None declared